Impeding the γ′ depletion during the interdiffusion between bond coatings and superalloys via introduction of tantalum in bond coatings - Xiaoyu Sun; Pimin Zhang; Johan Moverare; Xin-Hai Li; Luqing Cui; Ru Lin Peng (Materials & Design, 2023)
The use of aluminiferous coatings profoundly improves the service life of superalloys but leads to microstructural degradation of superalloys and thus loss of mechanical properties. In this study, we modified MCrAlY coatings by adding Ta to reduce the interdiffusion effect on substrate alloys. This strategy was verified by 2000 h/1100 °C oxidation tests in two Ta-containing MCrAlY-IN792 systems. The system with 3.3 wt% Ta MCrAlY exhibits an outstanding resistance to γ′ depletion in the substrate and comparable oxidation property in comparison with a reference system of Ta-free MCrAlY-IN792. Increasing Ta to 7.4 wt% results in reduced oxidation resistance. Thermodynamic simulations revealed the phase-transformation mechanism induced by initial interdiffusion, uncovering the cause of γ′ depletion in the substrate and the mechanism behind improving resistance to γ′ depletion by Ta addition.